2012
DOI: 10.1080/1068316x.2010.532129
|View full text |Cite
|
Sign up to set email alerts
|

Clothed and unclothed human figure drawings lead to more correct and incorrect reports of touch in children

Abstract: The purpose of the current study was to examine the effect of clothed and unclothed human figure drawings (HFDs) on children's reports of touch. Eighty 4/5-year-olds and 80 9/10-year-olds participated in a staged event in which measurements of their body parts (e.g. waistline) were taken. Specifically, they were touched on 10 different locations. Immediately or three weeks after the event, they had to report where they had been touched. Half of the children received a clothed HFD while the other half was provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Our result implies that legal professionals should not immediately resort to the use of these drawings as long as we have no clear answer about the circumstances when making drawings do or do not affect accuracy. In a sense, our results are related to work showing that other props such as dolls and human figure drawings also increase the reporting of erroneous details (e.g., Otgaar et al 2012). Future research should look more closely on whether drawing might foster the reporting of incorrect information by conducting studies similar as ours but including more realistic stimuli (e.g., interactive events).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Our result implies that legal professionals should not immediately resort to the use of these drawings as long as we have no clear answer about the circumstances when making drawings do or do not affect accuracy. In a sense, our results are related to work showing that other props such as dolls and human figure drawings also increase the reporting of erroneous details (e.g., Otgaar et al 2012). Future research should look more closely on whether drawing might foster the reporting of incorrect information by conducting studies similar as ours but including more realistic stimuli (e.g., interactive events).…”
Section: Discussionsupporting
confidence: 48%
“…Following this, children had to show on the human figure drawing where they had been touched. In one of our studies (Otgaar et al 2012), 4/5-year-olds and 9/10-year-olds were involved in a staged event in which measurements of 10 body parts (e.g., soles of the feet) were taken. Immediately or after a delay of three weeks, children had to report where they were touched.…”
mentioning
confidence: 99%
“…First, the accuracy of information is usually unknown in field studies, leading to the possibility that the added information produced by body diagrams and specific questions included false information that decreased the overall accuracy of reports. In fact, this is exactly what a laboratory study that mimicked the design of the field studies found (Otgaar, Horselenberg, van Kapen, & Lalleman, 2011). Second, children and adults alike tend to provide more information with additional recall attempts, so these studies do not reveal what children would have reported had interviewers shifted gears in some other way (for example, by taking a break or turning briefly to neutral topics) before asking additional questions.…”
Section: Body Diagramssupporting
confidence: 56%
“…This ability is very important in forensic interviewing (Korkman et al 2008). Therefore, for future research, in order to evaluate interviewing skills, researchers could design an experimental study with a staged-event paradigm to provide opportunity to pose follow-up questions based on previous disclosed information (London et al 2009;Otgaar et al 2012).…”
Section: Discussionmentioning
confidence: 99%